A developing model for clustering and ranking bank customers. (2015) - Sajjadi, Khalil; Khatami-Firuzabadi, Mohammad Ali; Amiri, Maghsud; Sadaghiani, Jamshid Salehi
Nowadays, there are a lot of customer-based companies and organisations, including banks, that are serving to present services and products to customers with different levels. Creating difference for various clusters of customers with ranking approach is done for obtaining different objectives. This paper has tried to cluster and rank the bank customers with developing RFM model from the perspective of facilities and deferred and making RFMLD model. Finally, by doing clustering process, it has put a vast domain of customers with an extensive spectrum into similar groups and has started ranking each cluster through simple weighted way. Explicating marketing policies peculiar to each cluster and determining target customers in private banking, company-based banking, customers club, campaign etc., through loyalty creation and preservation in them is one of this paper's applications.